Pengaruh Familiar Auditory Sensory Training (FAST) Terhadap Tingkat Kesadaran Pasien Stoke: The Effect of Familiar Auditory Sensory Training (FAST) on the Level of Consciousness in Stroke Patients - Purnama, Agus; Koto, Yeni (MPI Press, 2024)
Introduction: Familiar Auditory Sensory Training (FAST) is an intervention that involves playing recorded sounds familiar to the patient to stimulate the auditory sense and increase the level of consciousness. This study assesses the effectiveness of FAST in enhancing Glasgow Coma Scale (GCS) scores in stroke patients with impaired consciousness. Objectives: This study aims to determine the effect of FAST on improving the consciousness level in stroke patients who experience decreased consciousness. Method: This study used a quasi-experimental design with pretest and posttest measurements. The research subjects were stroke patients with decreased consciousness who received the FAST intervention. GCS scores were measured before and after the intervention to evaluate changes in the level of consciousness. Result: Data analysis showed that there was a significant increase in GCS scores after the implementation of FAST. Before the intervention, the average GCS score was 5.40, which increased to 6.40 after the intervention with a p-value of 0.006 < 0.05 and an effect size of 0.8 (strong effect). Conclusion: Familiar Auditory Sensory Training (FAST) was proven effective in increasing the level of consciousness in stroke patients with decreased consciousness, as evidenced by a significant increase in GCS scores. These results support the use of FAST as a non-invasive intervention to stimulate consciousness in patients with impaired consciousness.